Physical Education Instructors’ Perception on the Commission on Higher Education Memorandum Order 39, S.2021 in a Higher Learning Institution in the Philippines - Aquino, John Michael (Thai Journal of East Asian Studies, 2023)
The Commission on Higher Education (CHED) issued Memorandum Order (CMO) No. 39, Series of 2021 in the Philippines to strengthens the management of physical education teachers and promotes achievement of student learning outcomes by providing rules, standards and recommendations for physical education (PATHFIT) at the tertiary level. It outlines causes and objectives of changes in course environment aligned with revised general education curriculum as outlined in CMO 20, Series of 2013. This research assesses perceptions of physical education instructors (PEIs) about CMO 39. The goal is to evaluate its advantages and disadvantages based on respondent feedback. Also investigated was the implementation process in PE classes to understand potential effect on student learning outcomes. Qualitative research was done with narrative inquiry and purposive sampling with respondents being 12 PEIs at a higher learning institution. Data was gathered by face-to-face interviews, using the validated interview guide. Results indicated positive and negative perceptions of PEI in CMO 39, s.2021, which permits teachers to provide engaging activities for students, encouraging them to work to master subjects. It also helps universities meet CHED standards and offers students comprehensive education tailored to individual needs. Seminars and workshops may help teachers prepare for successful implementation of new curriculum. Guiding and supporting students is essential for success in physical education.